Making Up the Issue: The Judges' Role in Formulating Actions in the Crown Colony Period: Pharazyn v Smith (1844) - Dorsett, Shaunnagh (Victoria University of Wellington Law Review, 2010)
This article considers one of the key procedural innovations of the first Supreme Court rules – the making up of the issue – through the lens of the Supreme Court decision in Pharazyn v Smith (1844). Making up the issue referred to the process whereby pleadings were drafted in conference with the judge hearing the case. This contrasted with the English system of the time of a series of written exchanges between parties designed to identify the disputed issues of fact and law, and in which the role of the judge was essentially a passive one. Through Pharazyn v Smith we can see one of the ways in which judges sought to modify English laws to the circumstances of the colony, as well as the judges' role in shaping litigation, and hence law, in the infant colony.